Stable-isotope tracing reveals the role of corticosteroid receptors in driving cortisol-mediated central and peripheral glucose regulation in zebrafish - Antomagesh, Femilarani; Vijayan, Mathilakath M. (Frontiers in Endocrinology, 2025)
RationaleCorticosteroids play a crucial role in the stress-induced metabolic adjustments, and this stress response is conserved across vertebrates. In teleosts, cortisol is the principal glucocorticoid and regulates metabolic processes predominantly through the activation of the glucocorticoid receptor (GR). In zebrafish (Danio rerio), we recently showed that both the GR and the mineralocorticoid receptor (MR) are essential for stressor perception and metabolic regulation, especially related to glucose production and target-tissue glucose uptake. Here, we tested the hypothesis that GR and MR have distinct roles in modulating the tissue-specific glucose metabolism in response to cortisol stimulation during stress in fish.MethodsThis was tested using GR knockout (nr3c1−/−) and either wild-type or MR knockout (nr3c2−/−) zebrafish treated with cortisol to mimic a chronic stress condition. Stable isotope-labeled glucose (U-13C-glucose) was injected intraperitoneally, and the labeled intermediates were assessed to investigate the fate of the glucose carbon in the serum, liver, and brain. The metabolites in these tissues were analyzed using LC-MS to investigate the 13C incorporation across the metabolic pathway at a systems level.ResultsChronic cortisol stimulation enhanced glucose breakdown and its utilization in the TCA cycle for energy production. The GR and MR activation led to distinct and complementary effects on glucose utilization and the generation of TCA intermediates in the brain and liver, suggesting a tissue-specific role for these receptors in energy substrate partitioning during stress in fish.ConclusionOverall, our results underscore the roles of GR and MR activation in elevating circulating energy substrates and facilitating tissue-level oxidative capacity and biomolecule synthesis from glucose metabolism in response to chronic cortisol stimulation in fish.